2018
DOI: 10.1002/aur.2026
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Biomarkers for Autism Spectrum Disorder

Abstract: Autism Spectrum Disorder (ASD) lacks validated measures of core social functions across development stages suitable for clinical trials. We assessed the concurrent validity between ASD clinical measures and putative biomarkers of core deficits, and their feasibility of implementation in human studies. Datasets from two adult ASD studies were combined (observational study [n = 19] and interventional study baseline data [n = 19]). Potential biomarkers included eye‐tracking, olfaction, and auditory and visual emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 54 publications
1
29
1
3
Order By: Relevance
“…This contrasts with results of many previous studies in younger subjects which showed that the best predictor of autism was reduced eye region fixation time Klin et al 2002). Moreover, despite the association found between looking at the mouth and social communication skills (Del Valle Rubido et al 2018), there was no difference in fixation in the mouth between groups.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This contrasts with results of many previous studies in younger subjects which showed that the best predictor of autism was reduced eye region fixation time Klin et al 2002). Moreover, despite the association found between looking at the mouth and social communication skills (Del Valle Rubido et al 2018), there was no difference in fixation in the mouth between groups.…”
Section: Discussioncontrasting
confidence: 99%
“…In the assessment of concurrent validity of this study, we observed that reduced olfaction was associated with worse emotion recognition ability on both RMET (r = 0.54) and ASR (r = 0.40), possibly indicating greater impairments in their TOM capacity, as well as communication deficits in the ADOS communication domain (r = − 0.34) and in the inappropriate speech subscale of the ABC (r = − 0.32). Olfaction identification also correlated with the VIQ (r = 0.47) and FSIQ (r = 0.40) (Del Valle Rubido et al 2018 ). These subanalyses did not control for differences in IQ, thus, the contribution of IQ differences to these associations is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ABC-CT ET included nine paradigms in Feasibility, reduced to five in the Main Study: (1) activity monitoring, which includes both static images and dynamic videos of two adult actors playing with children's toys while gazing at each other or at their shared activity (Shic et al, 2011;Umbricht et al, 2017;Del Valle Rubido et al, 2018). (2) Biological motion preference, where two point-light displays are shown on either side of the screen, one displaying biological motion and one displaying a control condition of rotating or scrambled dots (Annaz et al, 2011;Umbricht et al, 2017;Del Valle Rubido et al, 2018). (3) Pupillary light reflex, in which a dark screen with a small fixation animation at the center is shown, then replaced briefly by a white screen, followed by the same dark screen with animation (Nyström et al, 2015).…”
Section: Eye Trackingmentioning
confidence: 99%